Reoperation on an Implant-Supported Restoration in the Maxillary Anterior Region to Correct a Complex Aesthetic Deficit - M. M. Figliuzzi; L. Parentela; A. Forte; D. Aiello (Case Reports in Dentistry)
Introduction. In an era in which patients are becoming more and more demanding and in which there are many ways to satisfy their needs, modern implantology must consider the correct management of soft tissues during treatment planning, aiming for both functional and aesthetic rehabilitation while creating a prosthetic construction that is in harmony not only with the natural dentition of the patient but also with their face. The patient who came to our notice had a rehabilitative prosthetic implant on the left central incisor area, which did not satisfy any functional or aesthetic parameter. Furthermore, he presented an altered passive eruption in the contralateral hemiarch. Materials and Methods. The prosthetic crown was removed, the tissues were studied, and the team decided to proceed with customizing a provisional restoration that would cause the soft tissues to descend. A surgical periodontal procedure was then performed to solve the altered passive eruption condition that was also compromising the aesthetics. In conclusion, a permanent prosthetic crown was fixed into place. Discussion. Using a periodontal approach that was both surgical and prosthetic, the patient was rehabilitated correctly regaining both functions and aesthetics. It is of fundamental importance that each step in the procedure is carefully programmed; otherwise, the risk of making mistakes increases and solving the problems becomes less simple or less immediate. In order to do this, one must bear in mind that certain clinical cases can apparently concern just one tooth, yet the mouth must be considered as a whole, both functionally and aesthetically. To perform an optimal implantology, the clinician should be an expert in periodontology so that they can plan and, should it be necessary, perform all the therapeutical options (surgical and nonsurgical) that can lead to the best possible result. Conclusions. The resolution of this complex clinical case has been documented in order to share useful advice for the resolution of analogous cases. We strongly advise that each proposed procedure be planned meticulously and that the periodontological aspect of the case never be separated from the prosthetic or the implantological aspects since the integration of the periodontal tissues is of vital importance for both the functional and the aesthetic results.